Understand the risk factors associated with non alcoholic fatty liver disease and changes in biochemical parameters in the patients: a prospective study - Shende, Atul; Chandra, Umesh Kumar; Gowda, Dharshan; Warkade, Vinay; Ganganpalli, Dattaprasad (International Journal of Advances in Medicine, 2020)
Background: The true prevalence of both NAFLD and NASH are elusive but estimates based on imaging and autopsy studies suggest that about 20-30% of the adults in United States and western countries have excess fat accumulation in the liver. About 10% of these, strictly speaking about 2-3% of the adult population fulfils the criteria of NASH. True prevalence of NAFLD in Indian patients is not known. So, this study was planned to look for current trend of NAFLD in Indian patients. Methods: This prospective observational study was conducted in the Department of Medicine on 65 patients with ultra-sonography finding of fatty liver disease with no history of alcohol, in one year study duration. Results: It is observed that maximum patients are of middle age from age 31-60 years comprising 76% of patients. Out of total patients, 34% and 66% were males and females respectively. Out of 65 patients, 45(69%) had obesity and maximum number of the patients had waist hip ratio and neck circumference more than the cut off value. Out of 65 patients, 19(29%) had hypercholesterolemia and 42(65%) had hyper-triglyceridemia. Out of 65 patients, 32(49%) had higher alanine transaminase (ALT) level and 17(29%) patients had higher AST level. Out of 65 patients, 29(45%) had the homeostasis model assessment of insulin resistance (HOMA-IR) less than cut off value (less than 2.25) and remaining 36(55%) were having HOMA-IR more than 2.25. The sensitivity for the cut off value for HOMA-IR is 72.7% and specificity is 49.1%. Conclusions: Obesity, neck circumference, and waist hip ratio are higher than its cut off value for both sex, insulin resistance evaluated through HOMA- IR directly relates to the causation of NAFLD but at some extents higher triglyceride levels are also associated but the values of ALT and AST levels did not give any clue in these cases of NAFLD.